LECTURERS’ PERCEPTION AND PREFERENCE FOR E-LEARNING IN UNIVERSITY OF DUTA BANGSA SURAKARTA DURING COVID-19 PANDEMIC - NUROHMAN; NURHAYATI (CV KULTURA DIGITAL MEDIA, 2021)
E-learning System in faculty of Compur Science University of Duta Bangsa Surakarta are used as a media support the campus learning process. This study aims to determine the relationship between content (content), the level of accuracy of the system (accuracy), format, easy of use, timeliness, organizational support, user attitudes towards the e-learning system and perceived attitude of top management on the level of satisfaction of using the e-learning system in faculty of Computer Science, University of Duta Bangsa Surakarta. This research is a descriptive study used technology acceptannce model (TAM) with modified End User Computing Satisfaction (EUCS) approach method. The results of testing and data processing from respondents were normally distributed, with the Kolmogorov-Smirnov test. The results of testing the data related to the 16 questionnaire questions also show that the data is valid and reliable. User satisfaction with the implementation of learning through the e-learning system during the Covid-19 pandemic is quite high, above 75% strongly agree, even from 8 items, 7 items on average are above 80% strongly agree. From the results of data processing the average is 4.11, which means the acceptance strongly agrees with the e-learning system 82.2%. Content occupies the highest satisfaction score of 89.2% and the lowest level of satisfaction is organizational support, the lecturer satisfaction rate is 76.4%.